High Expression of Cancer-Derived Glycosylated Immunoglobulin G Predicts Poor Prognosis in Pancreatic Ductal Adenocarcinoma - Cui, Ming (J Cancer, 2020)
Background: Cancer-derived immunoglobulin G (CIgG) has been detected in various cancers and plays important roles in carcinogenesis. The present study aimed to investigate its clinical significance in pancreatic ductal adenocarcinoma (PDAC). Methods: Using tissue microarrays (TMAs) and immunohistochemistry, we assessed CIgG expression in 326 patients who underwent surgical resection for PDAC. The associations between CIgG expression and clinicopathological features and clinical outcomes were analyzed. Functional experiments were also performed to investigate the effect of CIgG on PDAC cells. Results: High CIgG expression was related to poor tumor differentiation and metastasis during follow-up and was associated with poor disease-free survival (DFS) and overall survival (OS). A multivariate Cox regression analysis identified high CIgG expression as an independent prognostic factor for DFS and OS. The incorporation of CIgG expression improved the accuracy of an established prognosis prediction model for 1-year OS and 2-year OS. In vitro studies showed that knocking down CIgG profoundly suppressed the proliferation, migration, and invasion capacity of PDAC cells. Conclusions: CIgG contributes to the malignant behaviors of PDAC and offers a powerful prognostic predictor for these patients.